Storytelling in the Digital World: The Power of Narratives and Analogies to Demystify Emerging Technologies - Pai, Vijeta (Digital Repository of Theses - SSBM Geneva, 2025)
As businesses navigate through an increasing reliance on evolving technologies, it has become predominantly important to make technology accessible to people from different educational and cultural backgrounds. This paper presents an overview of emerging technologies and their role in the new evolving world, analyzing the interplay between two distinct genres of creative storytelling and technical writing, and examining the impact of analogies to proliferate comprehension and adoption of emerging technologies among people belonging to diverse backgrounds. It uses the Case Study Methodology, drawing from 207 responses to a Global survey conducted online, with participants from different backgrounds and exposure to emerging technologies. This is then followed by purposive sampling of 5 people belonging to different occupational backgrounds, who, after being presented with 8 analogies to explain cloud computing concepts, are engaged in short semi-structured video interviews. The questions are centered around their preferred analogy, narrative style and comfort with the storytelling format to understand technical concepts. It concludes by reinstating the fluidity of genre definition, importance of cultural positioning and ethical considerations in communicating technical concepts to people from different backgrounds, finally validating the benefits of using storytelling to develop a contextual understanding of emerging technologies, to increase their accessibility and impact